Pelatihan Seni Tradisi Meudike Berbasis Kearifan Lokal untuk Penguatan Karakter Siswa di SMPN 3 Ingin Jaya, Kabupaten Aceh Besar - Yuli Astuti; Samsuri Samsuri; Ilham Septian (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
This training aims to strengthen local wisdom-based character for students at SMPN 3 Want Jaya, Aceh Besar Regency with traditional meudike art material. This training was carried out using lecture methods, learning by doing, discussion and question and answer. The first training session was conducted directly by Syeh Medya Hus as a meudike expert and the second session was carried out with group training. The results of the training show that this training can positively contribute to strengthening the religious, social and responsible character of students at SMPN 3 Want Jaya which is reflected in their seriousness, sincerity, cohesiveness, cooperation, helping each other during the ongoing training process. Therefore, this training can continue to be developed both in formal and extracurricular learning processes at school to create a generation that loves cultural identity and national identity.